(untitled) (Revista Docentes 2.0, 2025)
The COVID-19 pandemic forced a shift from face-to-face instruction to Emergency Remote Teaching (ERT), highlighting the need for innovative strategies to maintain student engagement and support learning outcomes. The objective of this research was to explore the implementation of a game-based student response system (GSRS), Kahoot!, as an educational innovation to enhance grammatical awareness and engagement among first-year university students in an English teaching program in Chile. An investigation was conducted within the pragmatic paradigm, employing an inductive-deductive method, a mixed approach, and a sequential explanatory design, with convergent triangulation and a transversal cut. Data were gathered through quantitative measures from pre- and post-tests, as well as a Likert-type perception survey, and qualitative data from open-ended student responses. Thirty-five participants completed 14 weeks of grammar-focused Kahoot! Activities are delivered synchronously and asynchronously. Statistical analysis using the Wilcoxon signed-rank test revealed a significant improvement in post-test scores (p< 0.001), suggesting that the intervention positively influenced grammar performance. Perception data indicated that students found Kahoot! Enjoyable, motivating, and helpful in consolidating content and providing immediate feedback. Qualitative findings supported these results, with students reporting increased participation, reduced monotony, and enhanced focus. However, concerns about competitiveness, anxiety, and internet access were also noted. Despite these challenges, the results confirm the pedagogical potential of GSRSs, such as Kahoot! In online environments, especially in contexts where motivation and interaction are compromised. The study concludes that game-based learning tools can effectively promote grammatical competence and engagement in ERT contexts and encourages further research into their long-term impact and adaptability to diverse settings.